2018
DOI: 10.1002/hyp.13250
|View full text |Cite
|
Sign up to set email alerts
|

Stratification response of soil water content during rainfall events under different rainfall patterns

Abstract: Many researchers have studied the influence of rainfall patterns on soil water movement processes using rainfall simulation experiments. However, less attention has been paid to the influence under natural condition. In this paper, rainfall, soil water content (SWC), and soil temperature at 10-, 20-, 30-, 40-, and 50-cm depths were simultaneously monitored at 1-min intervals to measure the variation in SWC (SWCv) in response to rainfall under different rainfall patterns. First, we classified rainfall events in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Many studies have shown that soil moisture is affected by rainfall conditions (Roberts et al, 2005;Wang et al, 2018). Similar results were observed in our study; specifically, our findings indicate that soil moisture in all three treatments varied with the amount of rainfall during the monitoring period.…”
Section: Soil Moisturesupporting
confidence: 91%
“…Many studies have shown that soil moisture is affected by rainfall conditions (Roberts et al, 2005;Wang et al, 2018). Similar results were observed in our study; specifically, our findings indicate that soil moisture in all three treatments varied with the amount of rainfall during the monitoring period.…”
Section: Soil Moisturesupporting
confidence: 91%
“…The maximum and minimum SWC appeared in the 50‐cm and 280‐cm soil layers, with values of 11.4 and 8.6%, respectively. This results was due to the infiltration depth of a single precipitation event being 50 cm under normal conditions (A, Wang, Sun, Xue, & Kiem, 2018), whereas the annual cumulative infiltration depth of precipitation in the study area is less than 200 cm and the depth of Robinia pseudoacacia L . root is approximately 300 cm (Table 2).…”
Section: Resultsmentioning
confidence: 84%
“…The growth rate of poplar trees in the large diameter class appears to be less responsive to rainfall, potentially due to factors like root hypoxia or root decay arising from excessive moisture in such conditions. Additionally, future research should emphasize the impact of rainfall on soil moisture and the water absorption capability of tree roots in soils with varying thicknesses-areas that are worthy of investigation [62][63][64][65]. However, our study did not extensively delve into these particular aspects.…”
Section: Discussionmentioning
confidence: 95%